Vaccination strategies for high-risk and fragile populations in Lombardy (Italy): a region-wide assessment of hospital-based models and best practices - Odone, Anna; Vecchio, Riccardo; Brogonzoli, Luisa; Sala, Elisa; Vigezzi, Giacomo Pietro; Muzzi, Alba; Borriello, Catia Rosanna; Cereda, Danilo; Rizzardini, Giuliano; Venturi, Alessandro; Iardino, Rosaria (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Subjects with selected underlying medical conditions are at higher risk of infection and severe outcomes from vaccines preventable diseases. While most countries adopt life-course approaches to vaccination, high-risk group immunization programmes could maximize individual protection, while contributing to population health. The COVID-19 pandemic stimulated the planning and implementation of successful hospital-based high-risk groups’ immunization models. However, in Italy, high-risk subjects’ vaccine coverage is not actively monitored at the national or regional level, nor shared guidelines exist yet on hospitalbased immunization programmes.Study Design. The study reports findings from a region-wide assessment of the availability, characteristics, and setting-specific features of hospital-based immunization programmes for high-risk subjects in the Lombardy region.Methods. Fondazione The Bridge a not-for-profit organization based in Milan, in collaboration with the Prevention Unit of the Lombardy Region Directorate for Welfare, and the University of Pavia coordinated a project aimed at bringing together regional health institutions, key stakeholders, academic experts, scientific societies and patients’ associations to assess high-risk subjects’ barriers to vaccine uptake and inform preventive programmes and policies. In this context, we designed and implemented a survey to systematically map the existence and characteristics of hospital-based immunization programmes targeting high-risk subjects. The survey was proposed to all 115 hospital medical directions of the Lombardy region. Results. We collected data from 97 hospital medical directions, with a response rate of 85%. Among respondents, 24% were publicly managed hospitals, 17% were Scientific Institute for Research, Hospitalization and Healthcare (IRCCS) and 59% accredited